2017
DOI: 10.18632/oncotarget.17675
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequencing and large-scale genotyping identifies MT-ND4 gene mutation m.11696G>A associated with idiopathic oligoasthenospermia

Abstract: Genetic variants of mitochondrial DNA (mtDNA) were implicated to be associated with male infertility. Our previous whole mitochondrial genome sequencing and association study has identified two susceptibility mtDNA variants for oligoasthenospermia in Han Chinese men. In this study, we tested promising associations in an extended validation using 670 idiopathic oligoasthenospermia cases and 793 healthy controls to identify additional risk variants. We found that the genetic variant of m.11696G>A showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…This disease was diagnosed by a novel substitution at the position 8684C>T. Wu et al (2019) revealed that sperm mtDNA copy number showed more diagnostic power than mtDNA deletions for the sperm abnormality. Ji et al (2017) revealed that the variant 11696G>A exhibited significant higher frequency in idiopathic oligoasthenospermic Chinese men and this SNP was correlated with low sperm motility supporting the genetic susceptibility to oligoasthenospermia. Holyoake et al (1999) found a polymorphic T to C transition in the ATP6 gene and suggested that the failure of immature spermatids having this mutation to fully develop.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This disease was diagnosed by a novel substitution at the position 8684C>T. Wu et al (2019) revealed that sperm mtDNA copy number showed more diagnostic power than mtDNA deletions for the sperm abnormality. Ji et al (2017) revealed that the variant 11696G>A exhibited significant higher frequency in idiopathic oligoasthenospermic Chinese men and this SNP was correlated with low sperm motility supporting the genetic susceptibility to oligoasthenospermia. Holyoake et al (1999) found a polymorphic T to C transition in the ATP6 gene and suggested that the failure of immature spermatids having this mutation to fully develop.…”
Section: Introductionmentioning
confidence: 72%
“…In spite of this approved identification, published evidence for classifying the samples into normospermic, teratospermic, oligospermic and asthenospermic as listed in WHO (2010) criteria was presented herein. Ji et al (2017) and Liu et al (2017) identified the different infertility cases according to sperm count and motility. Asthenospermia was identified by reduction in sperm motility lower than 40% motile sperms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Lu et al (2015) showed in a largescale study that two-specific SNPs already associated with mitochondrial pathologies, m.16179C>T and m.12361A>G, were related to alterations in sperm count and/or sperm motility (Lu et al, 2015). The same team also demonstrated in 2017 that the m.11696G>A mutation was associated with a significantly higher risk of asthenospermia (Lu et al, 2015;Ji et al, 2017).…”
Section: Mtdna In Male Infertilitymentioning
confidence: 95%
“…Mutation of mtDNA is correlated to reproductive capacity [ 22 ]. The mtDNA genetic variants in the NADH dehydrogenase 1 (ND1) genes may cause decreasing activities of mitochondrial respiratory chain complexes [ 25 ]. Best to our knowledge, there has not yet revealed mtDNA mutation on post-thawed Kacang buck sperm, even in other livestock animals.…”
Section: Introductionmentioning
confidence: 99%